PARTICLE TRANSPORT PROCESSES AT SLOPE ENVIRONMENTS - EVENT DRIVEN FLUX ACROSS THE BARENTS SEA CONTINENTAL MARGIN - Thomsen C.; Blaume F.; Fohrmann H.; Peeken I.; Zeller U. (My University, 2001)
Recent studies of the vertical flux of organic matter into the deep ocean have prompted the search for key organic compounds (biomarkers) as tracers for its production, flux and burial into the sediment.Particulate matter was collected with sediment traps moored at the Barents Sea continental margin (75°11.78'N/12°29.21'E; water depth 2050m) at 610, 1840 and 1950m depth. The compositions of the organic material in the two bottoms near traps differ significantly. This difference cannot be the result of a change of the vertical sedimentation alone. A combination of biomarker analyses, quantitative microscopy and bulk parameter determinations on water and sediment trap samples is used in this study to demonstrate that a turbidity plume event at the shelf edge is a vehicle to transport organic and lithogenic particles at high velocities to the benthos of the lower continental margin. It is suggested that fine particles were advected into the trap at 1850m, whereas the coarser fraction of higher settling velocities, passing several resuspension loops entered the lower trap.
Keywords: BIOMARKER; CONTINENTAL MARGIN; PLUME EVENT; FAST CROSS-SLOPE PARTICLE TRANSPORT